THU0053 APREMILAST INHIBITS THE TGFî'1 MEDIATED TRANSITION OF CULTURED HUMAN SKIN FIBROBLASTS INTO PROFIBROTIC MYOFIBROBLASTS: IN VITRO STUDY. (June 2019) - Cutolo, Maurizio; Montagna, Paola; Martinelli, Giulia; Tardito, Samuele; Corallo, Claudio; Giordano, Nicola; Cozzani, Emanuele; Pizzorni, Carmen; Paolino, Sabrina; Patanè, Massimo; Sulli, Alberto; Alessandri, Elisa; et al.
Abstract : Background: Fibroblast-to-myofibroblast transition and extracellular matrix (ECM) overproduction represent fundamental events in chronic inflammation, that characterise several diseases, including psoriasis (1, 2). Transforming growth factor-β1 (TGFβ1), plays an important role as a profibrotic mediator (3). Phosphodiesterases (PDE)4 act as proinflammatory enzymes via degradation of cAMP. PDE4 are expressed in normal skin fibroblasts (Fbs) and overexpressed in psoriatic skin Fbs and myofibroblasts (2). Objectives: This study investigated how apremilast (an oral PDE4 inhibitor small molecule used for the treatment of psoriasis and psoriatic arthritis) might interfere with intracellular signalling for the fibroblast-to-myofibroblast transition and the synthesis of profibrotic ECM proteins induced by TGFβ1 in primary cultures of healthy human skin Fbs. Methods: Human skin Fbs were isolated from 7 voluntary healthy subjects after signing informed consent and EC approval. The cultured Fbs were stimulated with TGFβ1 10ng/ml alone or in combination with apremilast 1μM and 10μM for 4, 16 and 24 hours. Other aliquots of Fbs were also previously stimulated with TGFβ1 for 4 hours and then treated with apremilast 1μM and 10μM for 4, 16 and 24 hours always in the presence of TGFβ1. Genes and related protein expression of α-smooth muscle actin (αSMA), type I collagen (COL-1) and fibronectin (FN) were investigated by qRT-PCR and Western blotting (WB). Smad proteins (the main signal transducers for receptors of TGFβ1) and extracellular signal–regulated kinases (ERKs), which are implicated in mediating TGFβ1 effects, were investigated by WB after 15, 30 and 60 minutes of apremilast treatment combined with TGFβ1 stimulation. Results: Apremilast significantly downregulated the phosphorylation of Smad 2 and 3, at 15 minutes, and that of Erk1/2, after 30 minutes (p<0.05), both induced by TGFβ1 stimulation in cultured skin Fbs. Apremilast significantly downregulated the TGFβ1-induced increase in the gene expression of αSMA, COL-1 and FN at 4 and 16 hours, and the related protein synthesis at 24 hours (p<0.05) in cultured skin Fbs (treated in combination with TGFβ1). Similar effects were observed in differentiated myofibroblasts treated with apremilast. Conclusion: Apremilast inhibited the fibroblast-to-myofibroblast transition in vitro, as well as the profibrotic activity induced by TGFβ1 in cultured skin Fbs by downregulating specific intracellular signalling pathways Smad 2/3 and Erk 1/2. These results might partially explain some of the downregulating effects on skin Fbs overactivity during treatment of skin lesions of psoriasis and that of psoriatic patients with apremilast. Reference: [1] Clarke DL, et al. Fibrogenesis & Tissue Repair 2013, 6:20. 2. Schafer PH, et al. Cell Signal. 2016;28:753-63. 3. Carthy JM. J Cell Physiol.2018;233:98-106. Disclosure of Interests: None declared